Setting of free and prior informed consent to the protection of indigenous peoples’ rights to water resources in Indonesia - Jasim, Rahmi; Isra, Saldi; Warman, Kurnia; Andora, Hengki (Edelweiss Applied Science and Technology, 2025)
This study examines the implementation of Free, Prior, and Informed Consent (FPIC) as a framework for safeguarding the rights of indigenous communities over water resources in Indonesia. FPIC is recognized in international law as the right of indigenous peoples to grant consent voluntarily and without pressure, as stated in UNDRIP. However, Indonesian positive law has not explicitly regulated its implementation. This study highlights the tension between the State’s Right to Control (HMN) and indigenous communities’ customary rights, which frequently results in the neglect of their rights in managing water resources. Through a normative legal approach, this research evaluates existing legislative arrangements and practices, identifies conflicts, and offers FPIC as a solution to ensure justice and sustainability in water resources management. The results show that the implementation of FPIC can improve the protection of indigenous peoples’ rights, strengthen the synergy between the state and indigenous peoples, and support democratic and equitable water resources management.